Inleiding tot die belangrikste metodes in die moderne literatuurwetenskap - 'n Metodologiese benadering - Berg, B. H. J. van der (Koers, 1984)
The article opens with a brief discussion of the development of literary theory as an independent discipline in the twentieth century. The author then provides some theoretical background and discussion of two main streams of modern literary method: Positivism and Hermeneutics.